Kontribusi Usahatani Kakao terhadap Pendapatan Petani di Kabupaten Kolaka - Bananiek, Sri; Suharno, Suharno (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2010)
Southeast Sulawesi is one of the cocoa center production in Indonesia. The total area of cocoa in Southeast Sulawesi in 2005 is 192,008 ha. Cocoa production in Southeast Sulawesi is 126,813 tones. It is mean that productivity is 1.033 kg/ha. The experiment was conducted in the Lambandia Village, Kolaka in June 2006. The primary data obtained through structured interviews (directed / guide interview) using a questionnaire of 70 respondents, selected on the basis of land ownership strata. Interviews aimed to know the performance socio-economic of cocoa farming from the farmer respondents. Primary data processed and analyzed by economic analysis. The research result indicated that cocoa gives the dominant contribution to the total income of farmer households, which represents 93% of the total farmers' income